2022
DOI: 10.1080/19490976.2022.2044722
|View full text |Cite
|
Sign up to set email alerts
|

Increasing the diversity of dietary fibers in a daily-consumed bread modifies gut microbiota and metabolic profile in subjects at cardiometabolic risk

Abstract: Some cardiometabolic risk factors such as dyslipidemia and insulin resistance are known to be associated with low gut microbiota richness. A link between gut microbiota richness and the diversity of consumed dietary fibers (DF) has also been reported. We introduced a larger diversity of consumed DF by using a daily consumed bread in subjects at cardiometabolic risk and assessed the impacts on the composition and functions of gut microbiota as well as on cardiometabolic profile. Thirty-nine subjects at cardiome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 59 publications
0
26
0
Order By: Relevance
“…The compositional pattern changes in gut microbiota, such as the Firmicutes to Bacteroidetes ratio, in different CVDs risks have been the hot points of gut microbiota research. Importantly, most clinical studies have suggested that the diversity, richness and evenness of gut microbiota are closely associated with CVDs [ 602 , 603 ]. And some studies added bacteria to animals to observe the development of CVDs to explore the direct effect of gut microbiota on CVDs risk.…”
Section: Perspectivementioning
confidence: 99%
“…The compositional pattern changes in gut microbiota, such as the Firmicutes to Bacteroidetes ratio, in different CVDs risks have been the hot points of gut microbiota research. Importantly, most clinical studies have suggested that the diversity, richness and evenness of gut microbiota are closely associated with CVDs [ 602 , 603 ]. And some studies added bacteria to animals to observe the development of CVDs to explore the direct effect of gut microbiota on CVDs risk.…”
Section: Perspectivementioning
confidence: 99%
“…Using this approach, efforts have been made to define differences in the fine structure of fibers and relate these to the specific gut microbiota response and health outcomes ( 12 , 39 , 43 ). For instance, in a recent human trial wheat bread was enriched with a variety of fibers like wheat dextrin, micronized wheat bran, oat flakes and bran, inulin, locust bean gum and pectin, which to some degree decreased cholesterol, insulin and HOMA-IR levels and these changes were linked to an increase in the gut microbiota able to break glycosidic bonds ( 44 ). Similarly, another recent human trial in overweight individuals linked the gut microbiota’s ability to ferment arabinoxylan but not crystalline cellulose to an observed increase in satiety ( 45 ).…”
Section: Current View Of Dietary Fibers: Single Isolated Components A...mentioning
confidence: 99%
“…In case study 13 ( Table 1 ), a public-private partnership between the National Research Institute for Agriculture, Food and the Environment (INRAE, France) and a bakery (Bridor, France) has aimed to provide more fiber with their product Amibiote® (meaning biota friend), a new commercialized bread ( Ranaivo et al, 2022 ). The recipe includes 7 fibers rigorously selected based on the beneficial effects documented by the INRAE, while the company performed the technological development to provide a multi-fiber bread product that was non-distinguishable by eye from the control bread.…”
Section: Example Success Storiesmentioning
confidence: 99%
“…The consumption of the multi-fiber bread doubled the daily fiber intake in comparison to the control bread and contributed to promoting gut microbiota diversity and functions. Besides the nutritional qualities of this multi-fiber bread, it also showed ability to manage hypercholesterolemia and improve insulin sensitivity ( Ranaivo et al, 2022 ). This multi-fiber bread increased the Parabacteroides distasonis population, a gut bacteria documented for its anti-inflammatory and anti-obesity properties ( Cuffaro et al, 2020 ; Ezeji et al, 2021 ).…”
Section: Example Success Storiesmentioning
confidence: 99%